PERANCANGAN PERBAIKAN OUTBOUND LOGISTICS PROCESS GROUP DENGAN PENDEKATAN PLAN-DOCHECK-ACT DAN MULTI-MOMENT ANALYSIS - Innadziroh, Lu'lu
This study is intended to assess and evaluate waste that occurs in the outbound logistics process group area managed by the Logistics Division in one of the manufacturing companies located in Cikarang. In addition, based on the results of the waste evaluation obtained, further improvements were proposed to reduce waste and overtime in the Logistics Division. The Plan-Do-Check-Act (PDCA) cycle was chosen as a research framework on the basis of continuous improvement and the Multi-Moment Analysis (MMA) approach was chosen by considering the company that use job shop production systems. However, to conduct MMA requires a list of activities or business processes that run to manage the outbound logistics process group. In this case, the company does not have documentation of outbound logistics business processes, so business processes need to be mapped first. Furthermore, MMA is carried out with the principle of work sampling and wastes are evaluated. Based on the results of MMA, it was found that the level of waste in the form of non-value added (NVA) activities was 15,1%.